The Negative Impact of Sectarianism in the Novel Trespasses by Louise Kennedy: Dampak Negatif Sektarianisme dalam Novel Trespasses Karya Louise Kennedy - Serli Widianti (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2024)
This research aims to analyze the negative impacts of sectarianism in the novel Trespasses. Sectarianism is intolerance or hatred towards individuals or groups based on their differing religious or ideological beliefs. Sectarianism generally refers to socio-political and religious conflicts. The Trespasses contains sectarian conflicts between Catholics and Protestants, as well as between loyalists and republicans. Therefore, this research focuses on assessing the negative impact of sectarianism on the society. This research employs an objective approach that focusing on the data contained in the novel. The research method employs a qualitative, descriptive method to analyze the data in accordance with the formulation of the problem. The results of this study indicate four negative impacts of sectarian conflict: deterioration of relationships among the IRA members; changes in individual personalities; destruction of properties and loss of life; and the lack of accommodation leading to Protestant domination and the subjugation and discrimination of the Catholic communities.